2019 28th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2019
DOI: 10.1109/ro-man46459.2019.8956400
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Trust in Child-Robot Interaction

Abstract: In child-robot interaction, the element of trust towards the robot is critical. This is particularly important the first time the child meets the robot, as the trust gained during this interaction can play a decisive role in future interactions. We present an in-the-wild study where Polish kindergartners interacted with a Pepper robot. The videos of this study were analyzed for the issues of trust, anthropomorphization, and reaction to malfunction, with the assumption that the last two factors influence the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Significantly, the stronger the hedonic-related social presence they perceived, the greater the improvement in uneasiness. This result is also compatible with the view that social presence is a product shaped by the affective components that one senses during interactions [51], which could be more relevant in shaping children's negative attitudes about robots than the cognitive concerns of utility (e.g., [58,59]).…”
Section: The Increased Social Presence Attenuated Children's Pre-exis...supporting
confidence: 85%
See 1 more Smart Citation
“…Significantly, the stronger the hedonic-related social presence they perceived, the greater the improvement in uneasiness. This result is also compatible with the view that social presence is a product shaped by the affective components that one senses during interactions [51], which could be more relevant in shaping children's negative attitudes about robots than the cognitive concerns of utility (e.g., [58,59]).…”
Section: The Increased Social Presence Attenuated Children's Pre-exis...supporting
confidence: 85%
“…This latter pattern aligns more with children's relationships with the social robot. Even with preconceptions about the robots' capability, children were not noticeably troubled when robots failed expectations [58,59]. In this case, a higher initial image of social presence does not necessarily lead to greater disappointment in children.…”
Section: Regarding Rapport Building Children's Impressions Of a Robot...mentioning
confidence: 92%
“…Yadollahi et al [108] manipulated the type of error a robot made and identified children's ability to recognise the robot's mistakes (learning-by-teaching). Finally, Zguda et al [109] performed a qualitative analysis of children's reactions to a robot which showed a malfunction, suggesting that children either did not notice or did not care about the error of the robot. However, although robot errors were a manipulated variable in all these studies, quantitative measurements of trust were only included in the first two [31,101].…”
Section: Robot Errorsmentioning
confidence: 99%
“…Although some studies have addressed children's cognitive development with the support of robots [35], fewer have dealt with the impact of cognitive states on trust [21], where cognitive states refer to the children's perceptions of, and thinking about, a robot during and after their interaction with it (e.g., anthropomorphism and perceived support of the robot toward the child). In our previous study on developing trust in children towards the robot, we underlined the need to focus on a friendly, accessible design [36]. As trust and expectations relate to the experience of robot users while interacting with it, some studies [22] proposed a methodology for the design of robotic applications, including desired features, to avoid negative CRI experience, which may prevent children from further interacting with the robot and accepting it [37].…”
Section: Cognitive Statesmentioning
confidence: 99%